Evaluation of the Proximity of the Maxillary Teeth Root Apices to the Maxillary Sinus Floor in Romanian Subjects: A Cone-Beam Computed Tomography Study - Vlad Ionuţ Iliescu; Vanda Roxana Nimigean; Cristina Teodora Preoteasa; Lavinia Georgescu; Victor Nimigean (Diagnostics)
Background/Objectives: Among the paranasal sinuses, the maxillary antrum holds unique clinical relevance due to its proximity to the alveolar process of the maxilla, which houses the teeth. This study aimed to evaluate the position of the root apices of the maxillary canines and posterior teeth relative to the maxillary sinus floor in Romanian subjects. Methods: Data for the study were retrospectively obtained from cone-beam computed tomography (CBCT) scans. The evaluation considered the pattern of proximity to the sinus floor for each tooth type, comparisons of the sinus relationships of teeth within the same dental hemiarch, as well as those of homologous teeth, and variation in root-to-sinus distance in relation to sex and age. Nonparametric tests were used for statistical analysis, and multiple comparisons were performed using Bonferroni post hoc correction. Results: The study included 70 individuals aged 20 to 60 years. The distance to the sinus floor decreased progressively from the first premolar to the second molar, with median values of 3.68 mm (first premolar), 1.45 mm (second premolar), 0.50 mm (first molar), and 0.34 mm (second molar) (p < 0.01). Stronger correlations were observed between adjacent teeth than between non-adjacent ones. The distances to the sinus floor were greater on the right side compared to the left; however, these differences were not statistically significant (p > 0.05 for all teeth). Concordance between left and right dental hemiarches regarding the closest tooth to the sinus floor was found in 70% of cases (n = 49), most frequently involving the second molars (n = 38; 54.3%). On average, the distance from the sinus floor was smaller in males compared to females, with statistically significant differences observed only for the second molar. Increased age was associated with a greater distance to the sinus floor. Conclusions: Of all the teeth investigated, the second molar showed the highest combined prevalence of penetrating and tangential relationships with the maxillary sinus. At the dental hemiarch level, the second molar was most frequently the closest tooth to the sinus floor, and in the majority of cases, at least one posterior tooth was located within 0.3 mm. Accurate preoperative assessment of tooth position relative to the sinus floor is essential when performing non-surgical or surgical root canal therapy and extractions of maxillary molars and premolars. CBCT provides essential three-dimensional imaging that improves diagnostic precision and supports safer treatment planning for procedures involving the posterior maxilla.